Error Back Propagation Algorithm with Adaptive Learning Rate - Kolbusz, Janusz; Rozycki, Pawel; Lysenko, Oleksandr; Wilamowski, Bogdan M. (The International Conference on Information and Digital Technologies (Online), 2019)
Error Back Propagation algorithm is one of the most popular method for training artificial neural networks. Unfortunately, this is also one of the slowest due to constant and small learning rate parameter used to update weights of neurons. There are therefore many methods for dynamic change this parameter in the adaptive manner. In this paper has been presented new method based on estimation of learning rate with respect of approximation for the value of output error.